Can data visualization storytelling in energy communication campaigns ingrain farmers’ intentions to use agrivoltaic system? Evidence from global south - Raza, Syed Hassan; Ogadimma, Emenyeonu C.; Abdullah, Zulhamri; Khan, Shumaila; Raj, Sony Jalarajan; Jamil, Sadia; Malik, Aqdas; Alkhowaiter, Mohammed; Khan, Sajid Ullah (My University, 2025)
Purpose Innovative technologies pave the way to address alarming global climate issues. Among these technologies is the expansion of renewable and clean energy in farming, which aims to meet the global cheap energy demand and, at the same time, replace fossil fuels. In pursuant to this, agrivoltaic technology is an innovation that provides sustainable and low-cost production solutions to diminish the adversities associated with climate change and global warming. However, farmers from developing nations remain unacquainted or unenthusiastic about adopting such sustainable technologies. Therefore, in response to these key challenges related to climate change, this study aims to provide the utility of communication resources to inspire climate-friendly behaviors among farmers. Design/methodology/approach This study used a cross-sectional field survey method for data collection from 992 farmers. Findings The results verified that using data visualization storytelling in communication campaigns could significantly enhance farmers’ public understanding of adopting renewable technologies. Research limitations/implications Theoretically, results highlighted the importance of communication strategies in a downward spiral of ongoing challenges of optimal climate protection, counteracting rebound effects and reducing carbon emissions. Practical implications The novel contribution of this research by examining the data visualization storytelling in climate and energy communication campaigns paved the way for social marketers to develop a straightforward and user-friendly platform for implementing innovative renewable technologies. Originality/value This research underpinned a novel approach that remains understudied to understand how data visualization storytelling supports renewable technology adoption. Furthermore, it addressed the timely call for research on how data visualization storytelling can assist in achieving UNSD goals 12 and 13 by promoting renewable technologies among the farmers from the neglected area of the Global South.
Keywords: energy communication; data visualization; sustainable energy; agrivoltaic technology; energy production; media dependency theory